MENINGKATKAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENJAHIT POLA PADA KELOMPOK A DI TKIT BINA PRESTASI - Elis Mayasri; Tati Masliati (LPPM Universitas Bina Bangsa, 2023)
The progress of fine motor skills of children aged 4-5 years at TKIT Bina Prestasi has not resulted in the expected development of most in one class for the flexibility of children's fingers. Through sewing patterns of varying complexity and simplicity, it is possible for researchers to use them on the fine motor skills being learned. Because the lack of stimulating children's balance between fine motor skills such as tracing and various other activities such as tracing, drawing, cutting and pasting as well as hand-eye coordination in art learning activities makes their fingers flexible. So that these children's fine motor skills will prepare them better for independent tasks. This research was conducted in group A, where the task of the researcher worked according to the conditions faced by the class. This is shown by the fact that the majority of 5 out of 8 children have a stiff tendency when holding skills or objects with both hands. The methods used and research procedures include planning, implementing, observing, and reflecting. Data collection was carried out through observation and documentation, and percentage techniques were used to process the data. There are five meetings in each of the two research cycles. Through sewing activities, this study aims to improve children's fine motor skills. The results of the research cycle I while far from the standard of sewing mastery that has been determined then need to be adjusted. On the criteria for sewing mastery, children's fine motor skills increased in cycle II. Based on research, it shows that activities such as sewing patterns can support children in developing their fine motor skills